(untitled) (Journal of Health, Population and Nutrition, 2010)
This article reports the results of a qualitative study conducted in two villages of Matlab to explore the cultural dimensions of depression. Participants included adult men and women with and without a history of depressive episode (n=42), formal and informal healthcare providers (n=6), and caregivers (n=2). Adults (n=10) with a history of depressive episode were selected from a 2005 survey conducted by ICDDR,B. A case vignette was used for eliciting local terms for depression, perceived causes, impact, and treatments. Hardly anyone recognized the term bishonnota (literal translation of depression) used in the past survey. The participants thought that the vignette was about chinta rog (worry illness), and they spoke of somatic symptoms in relation to this condition. When explored further, they mentioned sadness and psychological complaints. Men felt that it affected them more while women felt the opposite. They associated chinta rog with poverty and social issues with impacts on marriage, work, and education. From their responses, it seemed that they preferred a psychosocial framework attributing the cause to thoughts and emotions, resulting from social causes. Commonly-suggested treatments were more income, better relationships, and tablets. Former health providers were often the first choice for help-seeking. The study hopes to ‘culturally inform’ the formal healthcare providers and programme planners. Key words: Culture; Depression; Perceptions; Qualitative studies; Bangladesh DOI: 10.3329/jhpn.v28i1.4528 J Health Popul Nutr 2010 Feb; 28(1): 95-106